2016
DOI: 10.1523/jneurosci.0299-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Strength of ERK1/2 MAPK Activation Determines Its Effect on Myelin and Axonal Integrity in the Adult CNS

Abstract: Myelin growth is a tightly regulated process driven by multiple signals. ERK1/2-MAPK signaling is an important regulator of myelin thickness. Because, in demyelinating diseases, the myelin formed during remyelination fails to achieve normal thickness, increasing ERK1/2 activity in oligodendrocytes is of obvious therapeutic potential for promoting efficient remyelination. However, other studies have suggested that increased levels of ERK1/2 activity could, in fact, have detrimental effects on myelinating cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
68
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 50 publications
12
68
0
Order By: Relevance
“…The major outcomes of the loss‐ and gain‐of‐function studies on the roles of mTORC1 and the upstream PI3K‐Akt and Mek‐Erk1/2 pathways in PNS and CNS myelination are summarized (Beirowski et al, 2017; Bercury et al, 2014; Carson et al, 2015; Cotter et al, 2010; Domenech‐Estevez et al, 2016; Figlia et al, 2017; Flores et al, 2008; Fyffe‐Maricich, Karlo, Landreth, & Miller, 2011; Fyffe‐Maricich, Schott, Karl, Krasno, & Miller, 2013; Goebbels et al, 2010, 2012; Ishii, Furusho, & Bansal, 2013; Ishii, Furusho, Dupree, & Bansal, 2016; Jeffries et al, 2016; Jiang et al, 2016; Lebrun‐Julien et al, 2014; Napoli et al, 2012; Newbern et al, 2011; Norrmén et al, 2014; Sheean et al, 2014; Sherman et al, 2012; Wahl et al, 2014; Zou et al, 2011, 2014)…”
Section: Myelination and Mtormentioning
confidence: 99%
See 1 more Smart Citation
“…The major outcomes of the loss‐ and gain‐of‐function studies on the roles of mTORC1 and the upstream PI3K‐Akt and Mek‐Erk1/2 pathways in PNS and CNS myelination are summarized (Beirowski et al, 2017; Bercury et al, 2014; Carson et al, 2015; Cotter et al, 2010; Domenech‐Estevez et al, 2016; Figlia et al, 2017; Flores et al, 2008; Fyffe‐Maricich, Karlo, Landreth, & Miller, 2011; Fyffe‐Maricich, Schott, Karl, Krasno, & Miller, 2013; Goebbels et al, 2010, 2012; Ishii, Furusho, & Bansal, 2013; Ishii, Furusho, Dupree, & Bansal, 2016; Jeffries et al, 2016; Jiang et al, 2016; Lebrun‐Julien et al, 2014; Napoli et al, 2012; Newbern et al, 2011; Norrmén et al, 2014; Sheean et al, 2014; Sherman et al, 2012; Wahl et al, 2014; Zou et al, 2011, 2014)…”
Section: Myelination and Mtormentioning
confidence: 99%
“…Although the interpretation of the available evidence is somewhat complex due to variable experimental strategies used, the combined findings suggest that, in contrast to hyperactivation of mTORC1 following deletion of TSC1 or TSC2 (Beirowski et al, 2017; Carson et al, 2015; Figlia et al, 2017; Jiang et al, 2016; Lebrun‐Julien et al, 2014), hyperactivation of Mek‐Erk1/2 using constitutively active Mek1 causes radial hypermyelination, both in the CNS and PNS (Fyffe‐Maricich et al, 2013; Ishii et al, 2013, 2016; Sheean et al, 2014). However, the mTORC1‐independent targets of Mek‐Erk1/2 that may be responsible for the differences observed by activation of these signaling pathways are unknown.…”
Section: Myelination and Mtormentioning
confidence: 99%
“…Enhanced expression of either Erk or Mek1 signaling in Schwann cells has also been shown to increase myelin thickness (Ishii et al . , ; Sheean et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Analogous to the core myelin genes expressed between oligodendrocytes and Schwann cells, the MAPK/ERK kinase (MEK)-Erk signaling pathway promotes myelination in both myelinating cell types. For example, in vivo studies have shown hypermyelination of axons in both the central and peripheral nervous system when the MEK-Erk pathway is constitutively activated (Ishii et al 2013(Ishii et al , 2016Jeffries et al 2016). We propose that identifying shared target genes in both Schwann cells and oligodendrocytes will shed light on potentially shared regulators of signaling mechanisms in myelinating glia.…”
mentioning
confidence: 95%
See 1 more Smart Citation